Metformin enhances cytotoxic action of dichloroacetate against Lewis lung carcinoma cells in vitro - Kolesnik, D.L.; Pyaskovskaya, O.N.; Gorbach, O.; Solyanik, G.I. (Experimental Oncology, 2023)
Summary. Tumor cell metabolism is considered one of the hallmarks of cancer. This concept is exploited in the development of new ways of anticancer therapy based on the use of substances capable of changing drastically bioenergetic metabolism of tumor cells. Among them, sodium dichloroacetate (DCA), an inhibitor of pyruvate dehydrogenase kinase, and metformin (MTF), an antidiabetic hypoglycemic drug, an inhibitor of the mitochondrial respiratory chain (complex I), both have been long used in clinical non-oncological practice, and presently are considered promising candidates in oncology. Aim: To study the capability of MTF to enhance the antitumor action of DCA against Lewis lung carcinoma cells in vitro. Materials and Methods: LLC/R9, a low metastatic variant of Lewis lung carcinoma cells, was used. Effects of 30 mM DCA in combination with 2 mM MTF on cell survival, cell cycle distribution, apoptosis, mitochondrial potential, intracellular ATP level, glucose consumption, and lactate production rates were determined in vitro. Results: MTF was shown to enhance the cytotoxic/cytostatic action of DCA against LLC/R9 cells in vitro. Treatment of LLC/R9 cells with 30 mM DCA in combination with 2 mM MTF resulted in a 39% decrease in the number of viable cells (p < 0.05), a 2.8-fold increase of the number of dead cells (p < 0.05), a near 2-fold decrease in the proportion of cells at the S-phase (p < 0.05), a 4-fold increase in the apoptosis (p < 0.05) and significant reduction (p < 0.05) of the mitochondrial membrane potential of tumor cells as compared to corresponding values in control. DCA alone reduced glucose consumption and lactate production rates by more than 26% (p < 0.05) and 34% (p < 0.05), respectively, whereas MTF counteracted these effects. Nevertheless, in the cells treated with both DCA and DCA in combination with MTF, the intracellular adenosine triphosphate increased by 33–35% compared with that in the control (p < 0.05). Conclusion: MTF enhanced the cytotoxic/cytostatic action of DCA against LLC/R9 cells in vitro, which points on their possible synergistic antitumor action in vivo.